Biosafety in Dental Practices Versus COVID-19 Outbreak - Ingrid Garcia Santos; Vívian Gonçalves Carvalho Souza; Guilherme Thomaz Verly da Silva; Aneliese Holetz de Toledo Lourenço; Laísa Araujo Cortines Laxe; Ana Carolina Morais Apolônio (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the dentists' knowledge about biosafety considering the SARS-CoV-2 and the risks of increasing the COVID-19 outbreak by dental practices during the pandemic in Brazil. Material and Methods: A cross-sectional study was performed by internet-based snowball sampling technique. A questionnaire with questions about different content was applied, and then analyzed the following two parameters: participants' Brazilian region and professional's specialty. Results: A total of 413 e-questionnaires from all Brazilian regions were considered valid. There were no significant differences among biosafety measures adopted by participants from different Brazilian regions (p≥0.05), except for those from North region, which have applied less previous oral antisepsis, temperature screening, and specific anamnesis tracking COVID-19 symptoms (p<0.05). The unique use of N95 mask was positively associated with North region (p<0.05). Expert participants of Groups 2 (oral surgery and correlate areas) and 4 (orthodontics, oral radiology and facial jaw orthopedics) were more updated than other ones (p<0.05). Conclusion: The biosafety protocols applied by participants were not adequate for the epidemiologic status of COVID-19 in each region of Brazil, from 13th May to 17th June 2020. Specialties linked to microbiology area or structured social networks have better applied preventive measures for COVID-19.